Writing content predicts benefit from written expressive disclosure: Evidence for repeated exposure and self-affirmation. Issue 2 (17th February 2016) - Niles, Andrea N.; Byrne Haltom, Kate E.; Lieberman, Matthew D.; Hur, Christopher; Stanton, Annette L.
Abstract : Expressive disclosure regarding a stressful event improves psychological and physical health, yet predictors of these effects are not well established. The current study assessed exposure, narrative structure, affect word use, self-affirmation and discovery of meaning as predictors of anxiety, depressive and physical symptoms following expressive writing. Participants ( N = 50) wrote on four occasions about a stressful event and completed self-report measures before writing and three months later. Essays were coded for stressor exposure (level of detail and whether participants remained on topic), narrative structure, self-affirmation and discovery of meaning. Linguistic Inquiry and Word Count software was used to quantify positive and negative affect word use. Controlling for baseline anxiety, more self-affirmation and detail about the event predicted lower anxiety symptoms, and more negative affect words (very high use) and more discovery of meaning predicted higher anxiety symptoms three months after writing. Findings highlight the importance of self-affirmation and exposure as predictors of benefit from expressive writing.